Successful management of a rare case of placenta percreta - Chaudhary, Aarushi; Antil, Sarvottma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Placenta accrete syndromes describe abnormally implanted, invasive or adhered placenta. Placenta percreta defines villi that penetrate through the myometrium and to or through the serosa. This abnormal placental in growth is identified, antepartum, by sonography. MR imaging can be used as an adjunct to sonography to define anatomy, degree of invasion, and possible ureteral or bladder involvement. A major decision concerns ideal institution for delivery. Planned delivery in a tertiary care facility is recommended. Timely antenatal diagnosis, plan and management can help prevent maternal morbidity and mortality.